Utilizing relational values to investigate a federally administered soil conservation programme in the US Northwest. Issue 1 (31st December 2023) - Pape, Timothy
ABSTRACT: Federal conservation programmes compensate property owners and farmers for sustained land-use practices which generate ecosystem services, yet enrolling participants can be a challenge. This paper studies that challenge in order to understand what values drive enrolment patterns in the Columbia River basin in the US Northwest, a region designated as a Critical Conservation Area by the US Department of Agriculture. Utilizing a relational values framework, the dynamics of the federally administered Conservation Reserve Program are explored. Findings are revealed through qualitative coding and analysis of semi-structured interviews and visual artefacts from programme participants, government employees and university-affiliated extension knowledge holders. This study concludes that five key relational values inform enrolment in this region beyond monetary reasons: stewardship, care, kinship, responsibility and identity. This paper posits that integrating information regarding relational values into federally administered conservation programmes may lead to more resilient and sustainable social–ecological systems.